The Failure of the American Dream in “The Great Gatsby”- Fitzgerald - Hodo, Zamira (European Journal of Multidisciplinary Studies, 2017)
The American Dream is one of the most important issues, which has drawn the attention of literary criticism through many years. It represents the ideals of a nation: equality, liberty, pursuit of happiness and democracy; ideals that have been understood in different ways by people. The real values related to these ideals changed and deviated from what it was meant into the enormous desire and greed for wealth and power. Fitzgerald tried to reveal that social discrimination is present and no one is treated as equal to others. The following research over the novel “The Great Gatsby” demonstrates how the dream cannot be successful because of the way it is misunderstood by the society and people’s materialism view of modern life. The characters and their attitudes through the chronology of the story are the embodiment of disappointment and the lack of moral values in the pursuance of a dream. Qualitative research used in this study aims to give a clear image and a deep analysis of the novel’s major themes, symbols, the period of writing, author’s life, various perspectives of the American Dream and its failure. We expect this thesis to be a good guide for further readings and projects with an explicit goal that the achievement of a dream does not necessarily requires the loss of the self and an excessive significance to what ruins the personal and the others future.